Exploring the Link between Supply Chain Capability and Inter-Organizational Compatibility: Do Inter-Organizational Information Systems (IOIS) Integration Matter? - Zaini, Syeliya Md; Saoula, Oussama; Ghani, Erlane K; Jalil, Nasir Abdul; Issa, Mustafa Rashid (International Journal of Supply Chain Management, 2019)
The prime objective of the current study is to the link between Supply chain capability and inter-organizational compatibility. In addition to that, the mediating role of the inter-organizational information systems (IOIS) integration in the relationship between the Supply chain capability and inter-organizational compatibility is examined. Using surveys-based methodology the data is collected with the aid of a questionnaire adopted from the previous studies. The SEM-PLS is used to analyses the data. Overall the findings of the study have provided support with the hypothesized results. The findings of the study confirm the view that the increasing role of globalization and growing environmental uncertainties have increased the managerial challenges in providing diversifying product and services to their values customer. The findings of the study also confirmed the argument broached in the study that the Integration of information systems across partnering organizations has become the backbone of supply chain management. Introduction. The study which is among very few studies on the issue will provide guidelines to policymakers, researchers and practitioners across the globe.